Positive reappraisals after an offense: Event-related potentials and emotional effects of benefit-finding and compassion*. Issue 4 (4th July 2017) - Baker, Justin C.; Williams, John K.; Witvliet, Charlotte V.O.; Hill, Peter C.
Abstract: Using a within-subjects design, three emotion regulation strategies (compassion-focused reappraisal, benefit-focused reappraisal, and offense rumination) were tested for their effects on forgiveness, well-being, and event-related potentials. Participants ( N = 37) recalled a recent interpersonal offense as the context for each emotion regulation strategy. Both decisional and emotional forgiveness increased significantly for the two reappraisal strategies compared to offense rumination. Compassion-focused reappraisal prompted the greatest increase in both decisional and emotional forgiveness. Furthermore, both reappraisal strategies increased positively oriented well-being measures (e.g. joy, gratitude) compared to offense rumination, with compassion-focused reappraisal demonstrating the largest effect on empathy. Late positive potential (LPP) amplitudes in response to unpleasant affect words were larger following the benefit-focused reappraisal strategy, indicating frontal LPP augmentation due to affective incongruence of the unpleasant stimuli with the positive, silver-lining orientation of the benefit-focused reappraisal emotion regulation strategy.